Older people’s motivations for participating in community singing in Australia - Lee, J.; Davidson, J.; Krause, Amanda (2016)
The aim of this project was to investigate the motivations of older people who regularly attend community singing groups in Australia. Four focus group interviews were conducted with 64 participants belonging to three community singing groups. Participants explained their motivation to attend and sing with others in the groups. A total of eight motivating factors were identified via an inductive thematic analysis, including (1) the importance of singing in my life; (2) enormous pleasure of singing with little pressure; (3) challenge and achievement; (4) spiritual and uplifting emotions; (5) strength in overcoming my age, disease and hardship; (6) good leadership; (7) fellowship with others; and (8) purpose and meaning of group singing. The themes were discussed from various perspectives including positive psychology and the PERMA well-being model. The findings suggest that the older participants seem to experience different motivation factors while at different stages of their engagement in the groups.